Strategi Pengembangan Desa Wisata di Kabupaten Bandung - Rachmaniar Rachmaniar; Renata Anisa (Pusat Riset dan Inovasi Nasional, 2025)
This study examines tourism village development strategies in Bandung Regency through a comprehensive literature review of three key articles: Jelekong Village, Lebakmuncang Village, and Baros Village. The primary objective is to identify common threads and differences in development approaches, and to analyze their relevance to tourism sustainability. The findings indicate that all three villages consistently utilize SWOT analysis as their strategic foundation. Tourism village development heavily relies on leveraging unique local potentials – be it natural, cultural, or agro-educational – realized through enhancements in attractions, accessibility, amenities, and activities. Active local community involvement forms the core of community-based development, ensuring environmental and cultural preservation. Furthermore, improved promotion, partnerships with various stakeholders, and innovation in tourism products and packages are crucial strategies. Local government support and human resource capacity building also play significant roles. The conclusion emphasizes that tourism village development in Bandung Regency requires a holistic synergy between local potential, community participation, and external support to achieve sustainability and visitor satisfaction.